Targeting ankle proprioception: A novel, valid, and reliable approach to measuring ankle proprioception for clinical implementation - Olson, Maxine L.; Miller, Steven A.; DiLiberto, Frank E. (Measurement : journal of the International Measurement Confederation, 2025)
•Our new laser-target measure of ankle proprioception demonstrated strong validity.•The measure demonstrated excellent within and between day reliability.•The measure is clinically feasible: low cost, small/portable, minimal time required. Ankle proprioception is vital to maintain balance but proprioceptive measurement is challenging in clinic. A new clinical measure of ankle proprioception, measuring joint position error (JPE), was designed and tested for validity and reliability. A total of 20 young healthy adults attended 2 visits. Subjects performed a repositioning task with a laser affixed to the foot, projected to a wall target, for all four planes of ankle motion. Laser JPE was calculated and validated against a 3D motion capture camera system. Average ankle laser JPE was 4.25° (±1.20) across all motions. Laser JPE was strongly associated with camera JPE, with over 95 % agreement. Laser JPE also showed excellent agreement within person and across days (ICC≥0.91). These strong results, combined with ease of setup and procedures, suggest our new measure of ankle proprioception is clinically feasible and appropriate.